Case Study on Determination of Selling Prices Based on Production Prices at A Medical Supplier in Makassar, Indonesia - Yosephina F. Ogot; Fransiskus E. Daromes; Kunradus Kampo (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This study aims to examine the accuracy of cost classification in the computation of the cost of goods manufactured and to determine the selling prices of Vipalbumin and Heparmin products at a medical supply company in Makassar. The research investigates whether the company's method for calculating the cost of production is accurate enough to set appropriate selling prices. A descriptive quantitative research method is employed for this analysis. The findings indicate that there exists a significant discrepancy in the calculation of production costs, which impacts the determination of selling prices. The recalculated cost of goods manufactured performed by the researcher is higher than the company's initial computation. This analysis reveals notable differences in production costs for the Vipalbumin and Heparmin products between the researcher and the company. Additionally, the results show a variance in selling price calculations made by the researcher and the company's figures. The analysis highlights that there is an incorrect classification of costs, particularly regarding packaging expenses—these costs are not accounted for in indirect costs but are mistakenly classified as marketing expenses. The implications of this research suggest that the company should refine its cost classification practices to ensure more accurate pricing strategies and improve overall financial decision-making.